DIKLAT PENYUSUNAN BAHAN AJAR BERBASIS TEKNOLOGI INFORMASI DAN KOMUNIKASI BAGI GURU RAUDHATUL ATHFAL - Yayah Kusbudiyah (Tatar Pasundan : Jurnal Diklat Keagamaan, 2019)
This article intends to examine the concept of education and training in the form of information and communication technology-based teaching materials for the athlete's teacher. This training is very important for them considering the teacher's low ability to use technology in the learning process. The research method used is the study of literature. The results of the analysis show that Substantive Technical Training in Teaching Material Preparation can be implemented to improve the competence of RA teachers in utilizing ICT-based learning media.Key Words:   Learning Media; ICT; Education and Training; Raudhatul Athfal